2018
DOI: 10.1186/s12876-018-0882-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic status and lifestyle factors associated with gallbladder polyps: a covariance structure analysis

Abstract: BackgroundGallbladder Polyps (GBP) are highly prevalent in China; however, the etiology of GBP has not been clearly defined. This study explored the associations between lifestyle factors and GBP and whether it mediated by metabolic factors or not.MethodsA total of 487 newly diagnosed GBP cases and 502 healthy controls were involved in this study. A questionnaire was used to investigate the socio-demographic characteristics and lifestyle factors. Food Intake Frequencies Questionnaire was used to obtain the foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…The prevalence of GPs for Chinese is approximately 6.9-9.5%, which is greater than that for Danish and Japanese populations (5)(6)(7)(8)(9). The pathophysiological mechanisms for gallbladder stones and GPs are different.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The prevalence of GPs for Chinese is approximately 6.9-9.5%, which is greater than that for Danish and Japanese populations (5)(6)(7)(8)(9). The pathophysiological mechanisms for gallbladder stones and GPs are different.…”
Section: Introductionmentioning
confidence: 97%
“…Most GPs are clinically diagnosed based on ultrasonography and only few undergo surgery to have histopathological confirmation. Most studies of GPs have focused on the prevalence or the associated risk factors; nevertheless, the clinicians are mainly concerned about the indication for surgery although the malignant potential of GP is quite low (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to identify the possible risk factors related to GBPs. Previous studies have suggested some factors related to GBPs, including male sex, middle age, hepatitis B surface antigen (HBsAg) positivity, cholecystitis, and glucose intolerance [3,[10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…USG is a noninvasive tool with greater than 90% sensitivity and speci city for diagnosing GB polyps [6]. The prevalence of GB polyps in Korea is estimated at 2.2 %-8.5 %, which is higher than that for Western countries but lower than the prevalence in China [7][8][9]. Although, most GB polyps are cholesterol polyps and benign lesions, the presence of GB polyps is used for the early detection of malignancy and to determine the appropriate time to undergo GB resection surgery [10].…”
Section: Introductionmentioning
confidence: 99%